1999
DOI: 10.1089/thy.1999.9.1163
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, Hypothyroidism, and Effect of Thyroid Hormone Replacement

Abstract: Elevation of total plasma concentration of homocysteine (t-Hcy) is an important and independent risk factor for cardiovascular disease. Hypothyroidism is possibly also associated with an increased risk for coronary artery disease, which may be related to atherogenic changes in lipid profile. Because hypothyroidism decreases hepatic levels of enzymes involved in the remethylation pathway of homocysteine, we prospectively evaluated fasting and postload t-Hcy in patients before and after recovery of euthyroidism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 22 publications
(15 reference statements)
3
26
0
1
Order By: Relevance
“…In univariate analysis the serum levels of thyroid hormones and TSH were significant determinants of plasma tHcy. These observations are consistent with the results of other authors [5,22,23]. Nedrebo et al demonstrated that tHcy level was significantly higher in patients with hypothyroidism, than in the group with hyperthyroidism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In univariate analysis the serum levels of thyroid hormones and TSH were significant determinants of plasma tHcy. These observations are consistent with the results of other authors [5,22,23]. Nedrebo et al demonstrated that tHcy level was significantly higher in patients with hypothyroidism, than in the group with hyperthyroidism.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is not in agreement with other authors [23,26]. Catargi et al found lower levels of folate in hypothyroid patients and in univariate analysis tHcy was significantly negatively associated with folate levels [22]. Recently, Ozmen et al reported low folate levels in hypothyroidism and concluded that hyperhomocysteinemia in hypothyroidism is associated with an altered folate status [34].…”
Section: Discussionmentioning
confidence: 70%
“…Against our study Catarqi et al in 1999 found that homocysteine level to be elevated in hypothyroid cases. 16 They postulated that hypothyroidism decreases hepatic levels of enzymes involved in remethylation pathway of homocysteine. Similarly Diekman et al concluded that plasma homocysteine levels increased in hypothyroidism.…”
Section: Discussionsupporting
confidence: 44%
“…Homocysteine is metabolized by one of the two pathways: remethylation and trans-sulphuration [1,2]. Hyperhomocysteinemia is an independent risk factor for atherosclerosis and atherothrombosis [3][4][5][6][7]. Although the molecular mechanism by which homocysteine or a related metabolite promotes atherothrombosis is unknown, the epidemiologic evidence of the association of hyperhomocysteinemia with atherothrombotic vascular disease is convincing [1].…”
mentioning
confidence: 99%